The Competitiveness and Carbon Leakage Effects of Carbon Pricing Evidence from EITE Manufacturing Firms in Indonesia - Riartri Nanda Bija; Bima Resi Pahlawan; Okky Putri Gunawan; Tantri Yuanika Sianipar; Bernat Joelsiman; Elisa Vania Yan (Journal of Economics Business Industry, 2025)
This study examines the effects of carbon pricing on industrial competitiveness and carbon leakage among energy-intensive and trade-exposed (EITE) manufacturing firms in the Jabodetabek metropolitan industrial cluster, Indonesia's largest industrial zone. Using an unbalanced panel of 423 firms and 2,687 firm-year observations from 2018 to 2024, we employ two-way fixed-effects regressions, instrumental variable estimation (IV-2SLS), and a difference-in-differences (DID) design exploiting the September 2023 launch of Indonesia's carbon exchange (IDXCarbon) as a natural experiment. We additionally quantify carbon leakage via a gravity model combined with multi-regional input-output (MRIO) analysis, and simulate the financial burden of the EU Carbon Border Adjustment Mechanism (CBAM). The results show that a one standard deviation increase in the effective carbon rate reduces total factor productivity (TFP) by 3.12 percentage points and decreases net profit margins by 1.89 percentage points. The DID estimate implies an 8.47 percentage point reduction in TFP for firms brought under the IDXCarbon scheme. The aggregate carbon leakage rate is 20.4%, with leakage split equally between domestic regional relocation and international displacement, driven predominantly by volume effects. Green innovation moderates the negative competitiveness effect, consistent with a partial Porter Hypothesis mechanism. The gap between Indonesia's effective carbon price (USD 3.9/tCO₂e) and the EU ETS benchmark (USD 70/tCO₂e) generates an estimated USD 291.8 million annual CBAM burden for Jabodetabek exporters, falling disproportionately on small and medium-sized enterprises. These findings provide robust empirical evidence for policymakers designing carbon pricing instruments that balance climate targets with industrial competitiveness in emerging economies.